(untitled) (Global Journal of Management and Business Research, 2014)
This research work seeks to explore the extent of Target Costing system adoption and implementation by manufacturing industry in South-Western Nigeria and the impact on their performance. In the research work, performance was defined in terms of profitability, Return on Capital Employed and reduction in the cost of production. The study adopted the survey research method, using structured questionnaire to collect data from the sample data group which represents all manufacturing firms in South Western Nigeria listed on the Nigerian Stock Exchange as at 31st December 2013. A total of 282 firms were included in the study. Reliability test with Cronbach’s Alpha of 0.88 was obtained using the ordinary least square and t-test methods. The results showed that the level of adoption and application of target costing by manufacturing industry in South Western Nigeria is low. However, the findings also showed that there is a strong positive relationship between adoption of Target costing and of improvement in Return on Investment and reduction of cost.